Counterproductive Counternarcotic Strategies? - Camilla Andersson (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2011)
We model the economic incentives surrounding opium crop production in Afghanistan. Specifically, we examine the impact of eradication policies when opium is used as a means of obtaining credit, and when the crops are produced in sharecropping arrangements. The analysis suggests that when perfect credit markets are available, an increased risk of eradication will lead to less land being allocated to opium poppy. However, when opium is used as a means of obtaining credit, the effects of eradication are no longer clear-cut. Finally, under sharecropping arrangements, increased risk of eradication will make the tenants worse off, while landlords may benefit.
Keywords: Q12; 330; Eradication; Informal credit markets; Opium; Sharecropping